2005
DOI: 10.1016/j.jmatprotec.2004.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Structure and hardness of titanium surfaces carburized by pulsed laser melting with graphite addition

Abstract: To cite this version:Bruno Courant, Jean-Jacques Hantzpergue, Ludovic Avril, Stéphane Benayoun. Structure and hardness of titanium surfaces carburized by pulsed laser melting with graphite addition. Titanium foils coated with graphite films 20 m thick were irradiated by means of a pulsed Nd-YAG in order to harden this metal by surface melting and alloying. The relationships between irradiation parameters, microstructure and hardness of the synthesized composite coatings were determined. Four relevant parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Many researchers reported that the carbide layer enables to increase hardness, wear resistance and corrosion resistance to titanium and its alloy (Kim et al, 2003). Sintered solid titanium carbide is a very important non-oxide ceramics that widely used in the fields of wear resistance tools and materials due to its high melting point (3170 o C), low density, high hardness (2500 ~3000HV), superior chemical and thermal stability, and outstanding wear resistance (Courant et al, 2005). Apart from sintering, titanium carbide layer can be created by other surface modification methods, such as plasma carburizing process, thermal carburization or high-temperature synthesis, carburization by laser melting, gas-solid reaction or gas carburization and sol-gel process , Yin et al, 2005, Cochepin et al, 2007, Luo et al, 2011.…”
Section: Carburization Of Titanium Alloymentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers reported that the carbide layer enables to increase hardness, wear resistance and corrosion resistance to titanium and its alloy (Kim et al, 2003). Sintered solid titanium carbide is a very important non-oxide ceramics that widely used in the fields of wear resistance tools and materials due to its high melting point (3170 o C), low density, high hardness (2500 ~3000HV), superior chemical and thermal stability, and outstanding wear resistance (Courant et al, 2005). Apart from sintering, titanium carbide layer can be created by other surface modification methods, such as plasma carburizing process, thermal carburization or high-temperature synthesis, carburization by laser melting, gas-solid reaction or gas carburization and sol-gel process , Yin et al, 2005, Cochepin et al, 2007, Luo et al, 2011.…”
Section: Carburization Of Titanium Alloymentioning
confidence: 99%
“…This process involved heating of specimen through continuous or pulse wave laser irradiation, rapid melting, intermixing or diffusion of carbon particle, and rapid solidification of the pre-deposited alloying elements on substrate to form an alloyed zone or carburized layer. Investigations on laser carburizing technique were extended from steel to -Titanium (Fouilland et al, 1997), commercial pure titanium (Courant et al, 2005) , and biomedical grade titanium (Sampedro et al, 2011). Laser melting carburization produces thick coating ranged between one and several hundred micrometers depending on the irradiation conditions.…”
Section: Carburization By Laser Meltingmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct Laser Fabrication (DLF) is a new rapid manufacturing process based on laser cladding and derived from welding, microwelding and laser technologies [1][2][3][4]. A power laser beam heats powder grains delivered from a coaxial nozzle system.…”
Section: Introductionmentioning
confidence: 99%
“…However, titanium boride (TiB) is well suited for use as reinforcement due to the absence of any intermediate phase between Ti and TiB [8][9][10]. Moreover, TiB reinforcement has certain desirable characteristics such as high elastic modulus, good thermal stability at high temperature and a density nearly equal to that of titanium [11].…”
Section: Introductionmentioning
confidence: 99%